METODE PENEMUAN HUKUM OLEH HAKIM - Bambang Teguh Handoyo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
In dealing with a problem, judges sometimes have difficulty resolving the matter because sometimes laws are incomplete or not clear, the judge must find and look for legal (rechtsvinding). Methods of legal discovery with the interpretation there are several types: (1) the interpretation subsumtif, (2) the grammatical interpretation, (3) the interpretation of systematic, (4) historical interpretation, (5) the interpretation soisologis or teleological, (6) the interpretation of comparability, (7) futuristic interpretation, (8) a restrictive interpretation, (9) an extensive interpretation. The method of the invention with the construction law there are 3 types, namely: (1) peranalogian argument or analogy, (2) the argument of a "contrario, (3) the rule of law pengkonkretan (rechtsvervijning), (4) a legal fiction. However, the judge's decision must be implemented in order to ensure certainty, truth and justice, so that judges are required to locate and find the justice that is in the community.